Specific dilation pattern in placental circulation and the NO/sGC role in preeclampsia placental vessels - Tang, Jiaqi; Zhang, Yumeng; Zhang, Ze; Tao, Jianying; Wu, Jue; Zheng, Qiutong; Xu, Ting; Li, Na; Xu, Zhice (Frontiers in Endocrinology, 2023)
Objects: Endothelial functions in controlling blood flow in placental circulation is still unclear. The present study compared vascular dilations between placental circulation and other vessels, as well as between normal and preeclampsia placental vessels. Methods: Placental, umbilical, and other vessels (cerebral and mesenteric arteries) were collected from human, sheep, and rats. Vasodilation was tested by JZ101 and DMT. Q-PCR, Western-blot and Elisa were used for molecule expressions. Results: Endothelium-dependent/derived vasodilators, including acetylcholine, bradykinin, prostacyclin, and histamine, mediated none or minimal dilation in placental circulation, which were different from that in other vessels from sheep and rats. There were lower mRNA expressions of muscarinic receptors, histamine receptors, bradykinin receptor 2, endothelial nitric oxide synthesis (eNOS), and less nitric oxide (NO) in human umbilical vessels when comparing with placental vessels. Exogenous NO donor (sodium nitroprusside, SNP) and soluble guanylate cyclase (sGC) activator (Bay41-2272) decreased the baseline of vessel tone in placental circulation from human, sheep, and rats, not in other arteries. sGC inhibitor ODQ suppressed the reduced baseline by SNP. The decreased baseline by SNP or Bay41-2272 was higher in placental vessels than umbilical vessels, suggesting that role of NO/sGC is more important in placenta. NO concentrations in preeclampsia placental vessels were lower than that in control, while no significant change was found in umbilical plasma between two groups. eNOS expression was similar between normal and preeclampsia placental vessels, but phosphorylated-eNOS were significantly lower in preeclampsia. Following serotonin, SNP or Bay41-2272-mediated dilations were weaker in preeclampsia placental vessels. The decreased amplitude by SNP or Bay41-2272 at baseline was smaller in preeclampsia. The decreased amplitudes by ODQ+SNP were comparable between two groups. Despite of higher beta sGC expression, sGC activity in preeclampsia placenta was lower. Conclusion: This study demonstrated receptor-mediated endothelium-dependent dilation in placental circulation was significantly weaker than other vessels in various species. The results showed firstly that roles of exogenous NO in regulating baseline tone of placental circulation were via sGC. Lower NO production and decreased NO/sGC could be one of reasons for preeclampsia. The findings contribute to understanding specific features of placental circulation and provide information in preeclampsia placental vessels.